ANALYSIS OF ASSIMILATION SOUND CHANGES IN THE SPEECH OF SEPATAN VILLAGE COMMUNITY, SEPATAN DISTRICT, TANGERANG REGENCY - Ajeng Novita Damayanti; Erwin Salpa Riansi; Sundawati Tisnasari (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This research examines changes in assimilatory sounds in the speech of the people of Sepatan Village, Sepatan District, Tangerang Regency. The scalpel used by researchers in analyzing this research uses Muslich's theory. This research aims to (1) How changes in assimilation sounds occur in the Sepatan Village community, (2) What factors influence changes in assimilation sounds in Sepatan Village, (3) What types of sound changes occur in the Sepatan Village community. This research uses qualitative research methods, the techniques used are interview techniques, note-free listening and follow-up techniques, namely recording techniques. Data analysis for this research uses Miles and Huberman's theory, namely an interactive model, starting from data collection, data reduction, data presentation and drawing conclusions or verification. The data source for this research is the speech of the Sepatan Village community. Based on the research results, factors were found that influence changes in assimilation sounds and 5 data of regressive assimilation, 5 data of progressive assimilation, 1 data of reciprocal assimilation, 10 data of phonetic changes, 1 data of phonemic changes.